The Role of Legal Origins in Improving Islamic Financial Services Access: Analysis Study of Arabic and Islamic Countries - لمزاودة, رياض (Finance and Business Economies Review, 2021)
This study seeks to examine the importance of legal origin in improving the financial system, and rise Islamic financial services access, and that by studying the role of Common Law, and Civil Law, and Shari’a Law in order the describe the various stages of financial development in Arab and Islamic countries. The results in this study indicate that most Araba and Islamic countries continued to rely on foreign legal systems, which has had a negative role due to an inability to create strong institutions that can enhance financial development levels and improve financial services access.